Recruiting women to a male-dominated activity : a case study of women's nonparticipation in fantasy sport - Ruihley, Brody J.; Grappendorf, Heidi (London : Human Kinetics, Inc., 2021)
Knowing that the fantasy sport industry is still growing and 81% of participation is by men (Fantasy Sports & Gaming Association, 2019), a fictional fantasy sport company, Fantasy Sports Connection, Inc. (FSC), and an employee, Molly Brinkmeyer, are utilized to present a case study on the lack of women participating in fantasy sport. FSC, in an attempt to offset financial concerns as growth in their fantasy sport offerings had plateaued, explores the idea of trying to market to and recruit more women to participate. They realize they need more data from women regarding their perception of fantasy sport so that they can strategize as to how to market to them and reposition their overall recruiting strategy. Armed with data, Molly found that women's perceptions of the activity consisted of the following: (a) the activity was time consuming; (b) the activity required research, surveillance, and information; (c) they had no interest in or understanding of it; (d) they felt the activity was too competitive; (e) they thought it was not real; and (f) they still had a positive opinion of fantasy sport. The case utilized theoretical research related to studies about (a) nonparticipation impressions in fantasy sport, (b) marketing to an underrepresented group, (c) gender-related constraints and barriers, and (d) the importance of repositioning associations and strategy.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Fantasy football (Game) -- Cast studies